THE INFLUENCE OF TECHNOLOGICAL, PEDAGOGICAL, AND CONTENT KNOWLEDGE (TPACK) OF ECONOMICS TEACHERS ON LEARNING MOTIVATION THAT IMPACTS LEARNING CREATIVITY IN ECONOMICS SUBJECT AT SMA NEGERI 59 JAKARTA - Yuliana, Dewi; Nurjanah, Siti; Zahra, Siti Fatimah (Transpublika Publisher, 2023)
This study aims to examine the impact of technological, pedagogical, and content knowledge (TPACK) of economics teachers on students' learning motivation and its subsequent influence on learning creativity in economic subjects at SMA Negeri 59 Jakarta. The research employs a quantitative approach with data collected through questionnaires from a sample of 107 students from class XI economics. The data analysis is conducted using SEM-PLS with SmartPLS software. The findings reveal significant direct effects of the teacher's TPACK ability on both student learning creativity (path coefficient: 0.335, t-statistic: 4.316, p-value: 0.000 < 0.05) and learning motivation (path coefficient: 0.378, t-statistic: 4.739, p-value: 0.000 < 0.05). Additionally, a significant direct effect of learning motivation on student learning creativity is observed (path coefficient: 0.315, t-statistic: 2.161, p-value: 0.031 < 0.05). Furthermore, the study also identifies an indirect effect of TPACK Ability on Learning Creativity through Learning Motivation, indicating a considerable influence (path coefficient: 0.119, t-statistic: 2.041, p-value: 0.042 < 0.05). Overall, these findings highlight the importance of economics teachers' TPACK in fostering students' learning motivation and creativity in economic subjects. The study provides valuable insights into the interplay between teacher knowledge, student motivation, and learning outcomes, contributing to the enhancement of educational practices and student engagement in the economics curriculum.